Innovation Of Use Of The Electronic Service Manufacturing Application (Nadine) In The Regional Office Of The Directorate General Of Treasure Of South Sulawesi Province - Muthmainnah, Nurjayanti; Nur, Andi Cudai; Yamin, Muhammad Nur (UNIVERSITAS PAKUAN, 2025)
This study aims to determine the Innovation in the use of the Electronic Official Manuscript Application (NADINE) at the Regional Office of the Directorate General of Treasury of South Sulawesi Province. This study is qualitative, therefore to achieve the objectives of the study, data collection techniques are used, namely observation, interviews and documentation. This study uses four indicators, namely Having Uniqueness, Having Characteristics or Elements of Renewal, Having a Planned Program, and Having a Purpose. The results of this study indicate that the Innovation in the use of the Electronic Official Manuscript Application (NADINE) at the Regional Office of the Directorate General of Treasury of South Sulawesi Province can be said to be